ARTIFICIAL INTELLIGENCE AS A GUARDIAN OF THE EUROPEAN UNION'S BORDERS: THE LEGAL FRAMEWORK AND THE ROLE OF FRONTEX (Heritage, 2025)
Artificial intelligence is rapidly changing and reshaping our daily lives, bringing undoubted benefits to humanity on the one hand and causing an avalanche of ethical questions on the other. The ethical "discourse" of the ever deeper introduction of artificial intelligence into all social streams points to the enormous dangers of the spread of discrimination, inequality and violations of human dignity, human rights and basic freedoms. After the adoption of the Regulation on artificial intelligence in the EU, the process of adjusting its use, especially the use of high-risk systems in many sensitive areas, including border controls, management of migratory flows and international protection of endangered categories of persons, began. The establishment of the legal framework for the use of artificial intelligence is part of a wider research on the connection between artificial intelligence and border controls, in which the authors focus on the legal, regulatory process of the Union in the introduction of the artificial intelligence system as an additional border guard together with the European Border and Coast Guard Agency ‒ Frontex. Using the historical method, the method of analysis of legal norms and the application of the teleological method, the authors indicate the beginnings of legal regulation of the use of modern technologies and how research and technological innovations evolved and became part of the Union legislation for the use of VI in border control. Then the direction of the research is focused on specific acts of secondary legislation with special emphasis on the Regulation or the Law on Artificial Intelligence. It indicates the classification and categorization of artificial intelligence systems for the area of ​​border control and security and their classification into high-risk systems in order to finally show the role of Frontex in current research and experimentation with artificial intelligence in order to achieve greater efficiency in the execution of border control tasks.
Keywords: artificial intelligence, EU legislation, border control, human rights, Frontex.